Kriminologi Dalam Era Digital Antara Perkembangan Kejahatan Cyber Dan Kesiapan Sistem Hukum - Tommy Adhiyaksah Putra; Reynaldo Setiawan; Alvi Syahrin Putra (Journal of Innovation Research and Knowledge, 2026)
Advances in information technology have transformed patterns of social interaction, economic transactions, and information dissemination, while at the same time creating new spaces for the development of cybercrime. Cybercrime is no longer limited to simple fraud but encompasses illegal access, data theft, identity theft, carding, digital extortion, the dissemination of fake news, hate speech, and other forms of crime that utilize computers and networks as either means or targets. This study aims to analyze law enforcement against perpetrators of cybercrime in Indonesia and the regulation of cybercrime within the Indonesian criminal justice system. The study employs a normative juridical method using a statutory approach and a conceptual approach, supported by a literature review of relevant books, journals, and legal sources. The findings indicate that law enforcement against cybercrime faces several challenges, including limited law enforcement capacity, digital forensic technology, laboratory facilities, investigation costs and time, as well as victims’ tendency not to report incidents. From a regulatory perspective, cybercrime provisions are dispersed across several legal instruments, requiring harmonization to keep pace with the characteristics of digital crimes, which are cross-border, rapidly evolving, and technology-based. Strengthening the legal system should be pursued through updates to legal substance, improvements in law enforcement structures, strengthening legal culture and digital literacy, and enhanced national and international cooperation. Victim protection should also be positioned as an integral part of cybercrime prevention and control policies